2017
DOI: 10.4172/2157-7587.1000265
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Stream Flow and Sediment Yield of Lolab Watershed Using SWAT Model

Abstract: The SWAT model was used to estimate the runoff and sediment yield of Lolab watershed. The model was calibrated, validated, and assessed for evaluation to model ambiguity using Nash-Sutcliffe coefficient (N SE ) and coefficient of determination (R 2 ). Ten highly sensitive parameters were recognized for stream flow simulation of which CN2 (Initial SCS CN II value) factor was the most sensitive one and four highly sensitive parameters were recognized for sediment yield simulation of which SPCON (Linear parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The literature suggests two sensitive parameters-the linear parameter (SPCON) and the exponent parameter (SPEXP)-for calculating sediment re-entrained in the channel [78]. Sediment routing was used to match the observed suspended sediment load and simulated sediment loads [67,102,103]. The model's default values of SPCON (=0.0001) and SPEXP (=1) were found to provide the best match between observed and simulated monthly sediment yields.…”
Section: Sedimentmentioning
confidence: 99%
“…The literature suggests two sensitive parameters-the linear parameter (SPCON) and the exponent parameter (SPEXP)-for calculating sediment re-entrained in the channel [78]. Sediment routing was used to match the observed suspended sediment load and simulated sediment loads [67,102,103]. The model's default values of SPCON (=0.0001) and SPEXP (=1) were found to provide the best match between observed and simulated monthly sediment yields.…”
Section: Sedimentmentioning
confidence: 99%
“…In SWAT hydrological modeling, the whole basin is segmented into separate sub-basins, which are then divided into different hydrological units [17]. The hydrological response unit (HRU) is the smallest component in a sub-basin of the hydrological model, which consists of land use, soil types, and slope defined by the modeler [18]. SWAT does not provide for spatial data input for modeling, and hence, ArcSWAT was introduced, which is the graphical interface connecting the SWAT model and ArcGIS that adds spatial data, such as digital stream network, land use/land cover, agricultural management practices, soil, and weather, and assigns simulation intervals [19].…”
Section: Description Of the Swat Modelmentioning
confidence: 99%
“…The use of RMSE as an objective function in automatic calibration has been reported by Boyle's et al [28] to yield a biased simulation. The underestimation might be due to the high sensitivity of the optimized model to peak flow events due to the use of RMSE as the objective function, because it squares the difference between the measured and the simulated streamflow [18]. The results of sediment calibration and validation showed good correlation with the calibration, which has an NSE value of 0.7 and an R 2 value of 0.9, and validation, which has an NSE value of 0.7 and an R 2 value of 0.8 (Tables 1 and 2).…”
Section: Calibration and Validationmentioning
confidence: 99%
“…Geomorphic studies of some watersheds have been analyzed using various geospatial techniques which revealed that Kashmir Valley is highly susceptible to environmental hazards such as erosion, landslides, and floods due to its complex topography and perplexed geography (Gull et al 2017;Rather et al 2017;Meraj et al 2018). Lidder watershed, being one of the biggest watersheds of Kashmir Valley, needs continuous monitoring and proper assessment for effective management of its land and water resources.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%